Comparison of holdings of NLM (CATLINE) with those of resource libraries. - Day, R A (1979)
The collection development practices of the National Library of Medicine (NLM), with the goal of comprehensive acquisition of biomedical monographs, are compared with those of the resource libraries of the TALON (Region IX) Regional Medical Library. Holdings of two resource libraries in the TALON region, The University of Texas Health Science Center at San Antonio and The University of Texas Medical Branch at Galveston, and of the TALON Union Catalog of Monographs were compared with the NLM CATLINE data base for four subject classes and selected imprint years. Foreign-language coverage is lacking in Region IX, with English-language coverage is lacking in Region IX, with English-language coverage ranging between 70 and 88% of titles listed in CATLINE. Absent English-language material tends to be ephemeral or otherwise out of scope for the resource libraries. Between 7.1 and 18.8% of monographs acquired in each subject class by the two recource libraries are lacking in CATLINE; this represents between 2 and 8% of the CATLINE titles for each class.